Spójność przestrzenna regionu a jego konkurencyjność - Markowska-Przybyła, Urszula (A Spatial Cohesion of Region Versus its Competitiveness, 2006)
Socio-economic cohesion is one of the priorities of national and European economic policy. The way of its achievement is to improve regional competitiveness i.e. equalise developmental chance. The aim of increasing to improve regional competitiveness of the spatial unit doesn't have to be at variance with the aim of decreasing inter- and intraregional disparities. The goal of the paper is to analyse competitive capacities of selected Polish regions and these intraregional disparities against this background as well as to present tendency of changes in 2000-2003.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 374-382